1890 Okla. Stat. 474, ch. 25, art. 38, § 4 - (:unkn) unknown (General Publisher, 1890)
Any person who keeps gunpowder or saltpeter outside of regulations is guilty of a misdemeanor.
--
Keywords: GUN POWDER STORAGE